The C(1)-C(α) torsional potential function of cis- and trans-3-fluorostyrene by supersonic jet spectroscopy - Hollas, J. Michael; Hussein, Mohd Zobir (Elsevier, 1989)
Single vibronic level fluorescence spectra of cis- and trans-3-fluorostyrene in a supersonic jet has resulted in the determination of several C(1)-C(a) torsional vibrational levels of both rotamers. Fitting these to a torsional potential function shows that the cis rotamer is the more stable by 220cm-1.